Detection of nerve fibers in the eutopic endometrium of women with endometriosis, uterine fibroids and adenomyosis - Garima Yadav; Meenakshi Rao; Meenakshi Gothwal; Pratibha Singh; Priyanka Kathuria; Prem Prakash Sharma (Korean Society of Obstetrics and Gynecology, 2021)
Objective The primary objective of this study was to establish the presence of nerve fibers in the eutopic endometrium of women with endometriosis and to determine whether these nerve fibers are exclusive to endometriosis or are also found in other pelvic pathologies associated with dysmenorrhea. Methods Endometrial tissue was obtained by aspiration (Pipelle), endometrial curettage, or following hysterectomy in women with endometriosis confirmed through histopathological examination, leiomyomas, and adenomyosis. The eutopic endometrium was subjected to immunohistochemical staining to detect PGP 9.5, which is a highly specific pan-neuronal marker. The nerve fiber density was correlated with the patient's pain score, as indicated by the Visual Analog Scale. A control group was formed by staining the endometrium of women presenting with dysmenorrhea but without the above-mentioned disorders. Results Nerve fibers were observed in sections of the endo-myometrium (in the deep endometrium) in 68% of patients with endometriosis who underwent hysterectomy or a deep endometrial biopsy. Nerve fibers were not observed in the aspirated endometrium of women with endometriosis. Only 13.7% of women with adenomyosis and 3.3% of women with fibroids had nerve fibers in their endometrium. Nerve fiber density was correlated with pain score in women with endometriosis. Conclusion Nerve fibers were found in the functional layer of eutopic endometrium in women with endometriosis; hence, we concluded that the presence of nerve fibers in the eutopic endometrium could diagnose endometriosis with a fairly good specificity of 92.7%. However, the absence of nerve fibers does not always exclude the disease.